2021
DOI: 10.1186/s12913-021-06564-4
|View full text |Cite
|
Sign up to set email alerts
|

From “stuck” to satisfied: Aboriginal people’s experience of culturally safe care with interpreters in a Northern Territory hospital

Abstract: Background Globally, interpreters are underused by health providers in hospitals, despite 40 years of evidence documenting benefits to both patients and providers. At Royal Darwin Hospital, in Australia’s Northern Territory, 60-90% of patients are Aboriginal, and 60% speak an Aboriginal language, but only approximately 17% access an interpreter. Recognising this system failure, the NT Aboriginal Interpreter Service and Royal Darwin Hospital piloted a new model with interpreters embedded in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 37 publications
0
58
0
Order By: Relevance
“…RDH is a 360-bed facility managed by the NT government’s Top End Health Service (TEHS), on Larrakia country in the capital of the NT. The pilot study was conducted at the inpatient renal unit where 84% of patients identified as Aboriginal [ 5 ]. Whilst English is the operational language of RDH, it is not the language most spoken amongst renal patients: 78% of Aboriginal renal patients spoke one or more of the 15 Aboriginal languages identified [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…RDH is a 360-bed facility managed by the NT government’s Top End Health Service (TEHS), on Larrakia country in the capital of the NT. The pilot study was conducted at the inpatient renal unit where 84% of patients identified as Aboriginal [ 5 ]. Whilst English is the operational language of RDH, it is not the language most spoken amongst renal patients: 78% of Aboriginal renal patients spoke one or more of the 15 Aboriginal languages identified [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pilot study was conducted at the inpatient renal unit where 84% of patients identified as Aboriginal [ 5 ]. Whilst English is the operational language of RDH, it is not the language most spoken amongst renal patients: 78% of Aboriginal renal patients spoke one or more of the 15 Aboriginal languages identified [ 5 ]. The most spoken languages were Yolŋu Matha and Tiwi, followed by Kunwinkju, Anindilyakwa and Kriol [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations